Development of History Learning Using Virtual Museum and Interactive Timeline to Strengthen Understanding of Bhinneka Tunggal Ika: Experimental Study - Nursyamsi Selfi; Qorry Nadhirotun Zahro; Resky Iswandi; Miftahul Janna; Alhuda Ladopura; Alya Salsa Ramadhani (Jurusan Teknik Informatika dan Komputer, 2024)
This study aimed to develop and evaluate an interactive history learning model using a virtual museum and digital timeline to strengthen students’ understanding of Bhinneka Tunggal Ika (Unity in Diversity) in Indonesia. Despite existing history education initiatives, students often struggle with conceptualizing historical events and connecting them to national values. This research addresses the gap by integrating immersive digital tools to enhance engagement, contextual learning, and value comprehension. A quasi-experimental design with pretest-posttest control group was employed. Participants were 120 high school students selected via stratified random sampling. The intervention consisted of a virtual museum tour combined with an interactive digital timeline, covering key historical events related to Indonesia’s cultural diversity. Data collection involved a structured knowledge test, a values comprehension questionnaire, and usability evaluation of the digital tools. The instruments were validated for content and reliability (Cronbach’s α > 0.85). Statistical analysis included paired-sample t-tests and ANOVA to compare learning outcomes between control and experimental groups. Results indicated significant improvement in students’ historical knowledge (mean gain = 22%) and comprehension of Bhinneka Tunggal Ika values (mean gain = 18%) in the experimental group compared to the control group (p < 0.01). Usability assessments showed high satisfaction scores (average 4.5/5), confirming the feasibility of virtual museum integration. The study demonstrates that virtual museum-based learning can effectively enhance historical understanding and national values. Limitations include short intervention duration and limited generalizability to other educational contexts. This research provides evidence for using immersive digital tools in history education to foster value-based learning. Future research may explore longitudinal impacts, scalability, and integration with other curriculum components.